The Spread of Plasmidic AmpC in a General Lebanese Hospital Over Nine Consecutive Years and the Relationship With Restricted Isolation Protocols - Fleifel, Mohamad; Machmouchi, Ahmad; Alameddine, Omar; Hoyek, Kim; Melki, Dimitri; Hallab, Elsa; Masri, Khalil; Sidaoui, Hiam R.; Stockman, David; Daoud, Ziad (Frontiers in Medicine, 2021)
Background: The dreaded bacterial infection by extended-spectrum β-lactamases (ESBL)-producers has always troubled the medical field whether on the public, scientific or clinical levels. One of the lesser known β-lactamases, which is capable of hydrolyzing broad and extended-spectrum cephalosporins – i.e. cephamycins plus oxyimino-β-lactams – are the AmpC β-lactamases. Such group, which has also been termed occasionally (and incorrectly) as ESBL Class C, confers resistance to β-lactamase inhibitors. The near-accurate prevalence of plasmidic AmpC-producing (pAmpCp) strains is possibly still a matter of debate considering the unevenly matched data between phenotypically-detected and molecularly-detected pAmpC. Aim: In the absence of any study in Lebanon addressing the AmpCp, our intention was to determine the incidence of AmpCp Enterobacteriaceae, especially plasmid-mediated ones, at the Centre Hospitalier du Nord (CHN), Lebanon and highlighting the importance of infection control protocols. Material and Methods: Carriage and infection with AmpCp Enterobacteriaceae were retrospectively investigated between 2011 and 2015 and prospectively between 2016 and 2019 at the Centre Hospitalier du Nord hospital- North Lebanon. The rise or decline in the numbers of such strains, in concordance with the allegedly intensive isolation of the patients, were analyzed. Results: ICU data is significant for an initial rise in infection isolates from 2012 to 2014 and in the carriage isolates from 2012 to 2013 with later notable overall decrease in the both isolates’ numbers with the application of the isolation protocols at CHN from 2014 onwards. Floors 2, 3, and 4 seemed to house the bulk of the isolates as well. Conclusion: Preventive measures, such as on-going surveillance of the hospital wards by specialized healthcare personnel and strict implementation of infection control practices, should be a top priority in any medical center in order to isolate such strains and try to put a limit for the development and the dissemination of any possible multidrug resistant strains.